The Behavioral Foundations of Strategic Decision-making: A Contextual Perspective - Maitane Elorriaga-Rubio (Copenhagen Business School (CBS), 2018)
The main aim of this dissertation is to shed light on the contextual aspects that intervene with achieving strategically key behavioral outcomes in decision-making. Each of the chapters constitutes an independent research study exploring one of the following behaviors which are of wide interest to organizations: the willingness to make brand-new partnerships, risk-taking, and decision-making performance. With my main focus on strategic decision-making under uncertainty, I propose and test more specific contextual conditions related to the cognitive processing and the content of the information that individuals and teams rely on when making choices. I combine theories from both social and cognitive psychology and strategic management. By adopting a multi-disciplinary perspective, this dissertation contributes to general and strategic management as well as the field of entrepreneurship. Furthermore, my research complements and moves forward the novel framework of “behavioral strategy”. This dissertation comprises of three experimental studies. The first study explores the role of positive and negative mood states as antecedents of a willingness to make brand-new partnerships under highly uncertain circumstances, and it proposes that the type of cognitive processing involved is an important moderator. The second study focuses on the influence of collective efficacy on risk perception and risk-taking by start-up teams in the context of inter-team competition. The study finds that these relationships are contingent on what type of performance aspirations an individual team has. Finally, the third study focuses on the moderating effect of both mood states and types of aspirations on explaining performance differences between overconfident decision-makers in overall competitive and uncertain situations.
hdl:10398/9669
Keywords: 650